Mourning the Human? Posthuman Death and Ontological Vulnerability in Jeff VanderMeer’s The Southern Reach Trilogy - Ferrández-Sanmiguel, María (International Journal of English Studies, 2024)
This article reads Jeff VanderMeer’s The Southern Reach trilogy from the perspectives of critical posthumanism and trauma theory, paying particular attention to how the two discourses perceive the relationship between self and other, the vulnerability of the human and the expectation of death. The discussion is articulated against the background of the trilogy’s explicit concern with the reconfiguration of the human and with the Anthropocene. This is carried out through an exploration of classical and recent definitions of trauma after its encounter with environmental degradation and under the threat of human extinction. As it is contended, the trilogy invites us to imagine an end to humanity that is not also the end of life on the planet. While this might be read in the key of horror or induce feelings of anxiety or mourning, it compels us to confront the ethical implications of our embeddedness to the natural world and our shared vulnerability. The article ultimately argues in favor of the power of the imagination to spark change.